Interaction between DNA and Trimethyl-Ammonium Bromides with Different Alkyl Chain Lengths - Chao Cheng; Shi-Yong Ran (The Scientific World Journal)
The interaction between λ—DNA and cationic surfactants with varying alkyl chain lengths was investigated. By dynamic light scattering method, the trimethyl-ammonium bromides-DNA complex formation was shown to be dependent on the length of the surfactant’s alkyl chain. For surfactants with sufficient long alkyl chain (CTAB, TTAB, DTAB), the compacted particles exist with a size of ~60–110 nm at low surfactant concentrations. In contrast, high concentration of surfactants leads to aggregates with increased sizes. Atomic force microscope scanning also supports the above observation. Zeta potential measurements show that the potential of the particles decreases with the increase of surfactant concentration (CTAB, TTAB, DTAB), which contributes much to the coagulation of the particles. For OTAB, the surfactant with the shortest chain in this study, it cannot fully neutralize the charges of DNA molecules; consequently, the complex is looser than other surfactant-DNA structures.